ANALISIS PENERAPAN AKUNTANSI DAN KESESUAIANNYA BERDASARKAN PSAP NO 07 TERHADAP ASET TETAP PADA DINAS PENGELOLAAN KEUANGAN DAN KEKAYAAN DAERAH DI KAB. ACEH TENGAH - Bahgieni Isma; Muhammad Saleh (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this study was to find out how the application of accounting to fixed assets was carried out by the Regional Financial and Wealth Management Office (DPKKD) of the Regency. Central Aceh and to find out whether the DPKKD Kab. Aceh Tengah has implemented fixed asset accounting in accordance with the Statement of Government Accounting Standards (PSAP) No 07. This type of research is descriptive qualitative research. The data used in this study are primary data and secondary data obtained by interview techniques and documentation. The results of this study indicate that the District DPKKD Aceh Tengah has treated its fixed assets in accordance with PSAP Number 07 in terms of recognition, assessment and reporting of fixed assets.